Synthesis of Visible Light Responsive N Doped TiO2 Photocatalyst and its Enhanced Photocatalytic Activity - Zhao, Yujie; Li, Huayang; Bala, Hari; Chen, Jingkuo; Zhang, Bowen; Fu, Xinglin; Fu, Wuyou (Current Nanoscience, 2015)
The N doped TiO2 (N-TiO2) photocatalyst was prepared by a sol-gel method using ammonium nitrate (NH4NO3) as solid substrates and doping source. The thermal dissociation of NH4NO3 during heat treatment process of dried gel can introduce N element to TiO2 promoting the crystal transformation and adjusting the band structure. Meanwhile, the N-TiO2 samples have large specific surface area and well mesoporous structure. The doped N element narrow the band gap of TiO2 and its light absorption edge has been broadened to visible region. The photocatalytic degradation measurement exhibit that the N-TiO2 sample show high photocatalytic activities in decolorisation of RhB under visible light irradiation. The kinetic calculations reveal that photocatalytic reaction rate constant for N-TiO2 is approximately 3 times higher than that for pure TiO2.
Keywords: TiO2